An adaptive modal pushover analysis procedure (VMPA-A) for buildings subjected to bi-directional ground motions - Yüksel, Ercan; SÜRMELİ, MELİH (My University, 2018)
A new modal pushover analysis procedure (VMPA-A) is developed and implemented in MATLAB code for three-dimensional buildings subjected to bidirectional ground motions. VMPA-A uses stepwise force patterns to represent changes in the dynamic characteristics because of the accumulated structural damages. The hybrid-spectrum concept is introduced to account for the bidirectional ground motion effects. Due to enactments of the equal displacement rule and the secant stiffness-based linearization process, nonlinear analysis is performed for specific displacement targets without stipulation of full modal capacity curves for each mode. Horizontal components of an earthquake record are considered simultaneously, and the consistency between the force and displacement vectors for each mode is provided. These are the main advantages of the proposed procedure against modal pushover analysis (MPA). An existing 21-story reinforced concrete building is analyzed to exemplify VMPA-A. The response parameters such as displacements, story drifts, internal forces, strains, etc. are discussed by comparing the results of VMPA-A with nonlinear time history analyses, which is accepted as the ‘‘exact solution’’. Though consistent demand estimations are obtained for story drifts, displacements and deformations, some conservative results are obtained for story shears.
Keywords: Adaptive pushover; Multi-mode pushover; Modal pushover; Higher mode effects; 3D; Torsion; Bi-directional earthquake; NONLINEAR STATIC ANALYSIS; BI-AXIAL EXCITATION; ASYMMETRIC BUILDINGS; SEISMIC DEMANDS; TALL BUILDINGS; PLAN BUILDINGS; COMPONENTS; SYSTEMS